Numerical and Experimental Investigation of Performance and Flooding Phenomena of a PEM Fuel Cell with and without Micro-Porous Layers - Ha Hiep, Nguyen; Duong, Vu (Engineering, Technology & Applied Science Research, 2024)
This work presents the results of manufacturing a single Proton Exchange Membrane Fuel Cell (PEMFC) with Micro-Porous Layers (MPLs) and an active area of 25 cm2, and the experimental study required to build its polarization curve. Based on the physical model data, a numerical model of this PEMFC is created in the ANSYS PEM Fuel Cell module. Numerical simulations were performed with boundary conditions consistent with the experimental conditions on the test station. The calculation and experimental result comparison of the polarization curves for voltages ranging from 0.29 V to 0.94 V proved that the utilized numerical model is highly reliable. The simulation of PEMFC without MPLs was conducted according to other stable input parameters and boundary conditions. The results show that the PEMFC performance decreases significantly due to the flooding phenomenon inside PEMFC without MPLs compared to PEMFC with MPLs. Such phenomena are challenging to observe experimentally. Numerical modeling can be further used to optimize the fuel cell components.